Pengembangan Media Interaktif untuk Penyelesaian Sistem Persamaan Linear Metode Eliminasi Gauss Berbasis Matlab Guide pada Program Studi Pendidikan Matematika - Primajati, Gilang; Oktavihari, Dita; Supiarmo, M. Gunawan (Jurnal el-Huda, 2025)
This study aims to develop an interactive learning media in the form of a GUI (Graphical User Interface) application using MATLAB GUIDE to solve Systems of Linear Equations (SLE) through the Gaussian elimination method. The research method employed is descriptive qualitative with a software development approach, encompassing stages such as needs analysis, interface design, algorithm implementation, and documentation. The developed application enables users to input the coefficients and constants of the SLE, compute the solutions using Gaussian elimination, and display the results in both numerical and visual forms (2D and 3D graphs). The research findings show that the application can solve SLE automatically, quickly, and accurately, and features a simple, user-friendly, and practical interface, as reflected by a practicality questionnaire score of 96.1%. This media is expected to serve as a supportive tool in mathematics education, particularly in enhancing students’ understanding of SLE concepts in mathematics education programs.